Routine determination of benzo[ a]pyrene at part-per-billion in complex industrial matrices by multidimensional liquid chromatography - Champmartin, C.; Simon, P.; Delsaut, Ph; Dorotte, M.; Bianchi, B. (Journal of Chromatography A, 2007)
A rapid and selective high performance liquid chromatography (HPLC) method using a column-switching technique has been developed for the determination of benzo[ a]pyrene in complex mixtures containing polycyclic aromatic hydrocarbons. The diluted sample is directly injected into the chromatographic system without pre-treatment. The purification is performed on-line using three cleaning columns filled with various stationary phases. The sample preparation, a simple dilution, and the analysis time do not exceed 45 min. The method developed was used to analyze industrial products such as oil, bitumen, etc. and was compared with an off-line method requiring treatment and extraction steps before the analysis.